Food microbiology : principles into practice - Erkmen, Osman, 1955-; Bozoglu, T. Faruk, 1950- (John Wiley & Sons, 2016)
This book covers application of food microbiology principles into food preservation and processing. Main aspects of the food preservation techniques, alternative food preservation techniques, role of microorganisms in food processing and their positive and negative features are covered. Features subjects on mechanism of antimicrobial action of heat, thermal process, mechanisms for microbial control by low temperature, mechanism of food preservation, control of microorganisms and mycotoxin formation by reducing water activity, food preservation by additives and biocontrol, food preservation by modified atmosphere, alternative food processing techniques, and traditional fermented products processing. The book is designed for students in food engineering, health science, food science, agricultural engineering, food technology, nutrition and dietetic, biological sciences and biotechnology fields. It will also be valuable to researchers, teachers and practising food microbiologists as well as anyone interested in different branches of food.- Resumé vydavatel
Keywords: potravinářská mikrobiologie; konzervování potravin; výroba potravin; food microbiology; food preservation; food production; elektronické knihy; sborníky; electronic books; papers of several authors